Agricultura familiar e agroecologia: um caso de desenvolvimento econômico no semiárido alagoano - Silva, Danessa Rafaella da (Universidade Federal de São Carlos, 2019)
This research was developed in the state of Alagoas, precisely in the backlands, in the municipality of Pão de Açúcar, where the Association of Producers in Agroecology - APAOrgânico is located. This association has set up as a reference in the semiarid region, because your associated farmers through social technology - PAIS (Sustainable Integrated Agroecological Production) started an journey of production free of chemical additives,where part won their participation as producers of the Social Control Organization. The APAOrgânico has 29 members, however, 22 active as producers who access government programs: Food Acquisition Program - PAA and National School Feeding Program - PNAE, and others who also participate in the free fair of the referred municipality. This way up, the research a general objective of is to evaluate the role of agroecology in the socioeconomic conditions of family farmers members of the Association (APAOrgânico), AL. As the chosen methodology, has a case study by means the approach the qualitative and quantitative approach, and for the obtaining of these data were applied semi-structured forms the 11 farmers in addition to technical visits the productive units. And, from this primary methodology and secondary research, it is possible to highlight some results as: of the 1,539 agricultural establishments of the municipality of Pão de Açúcar, only 3.45% used some type of pesticide in their properties; the population served by social technologies water access presents 4,156 families and 17,802 people (water for production) and 100,756 people (water for drinking) in Alagoas; After insertion in the PNAE and PAA programs, 66.67% of farmers declared that family food increased in quantity and quality improvement; they were analyzed the forms of obtaining of monetary income in addition to the income of institutional channels; Data obtained from non-monetary income vary from R$ 832.00 to R$ 69,313.00. The main conclusions of the present study show that public policies will always be part of rural development and that long-term economic and environmental sustainability will be realized by enhancing agroecological family farming.
Family agriculture and agroecology: a case of economic development in the alagoan semiarid
Keywords: Associação; PAA e PNAE; Renda; Autoconsumo; Tecnologia Social; Association; Income; Self-Consumption; Social Technology; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL